PENGELOLAAN ASET DAERAH (KAJIAN PADA KENDARAAN OPERASIONAL ANGGOTA DPRD PROVINSI RIAU PRIODE 2009-2014) - Syarasweti, Sari; Asrida, Wan (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2019)
Management of Regional Property in the Riau Provincial Government environment still experiences many obstacles and obstacles, especially in the administration of regional property so that optimality in the management of regional property has not been achieved, therefore the Government of Riau Province through Riau Provincial Regulation number 4 of 2003 concerning the Principal -Main Regional Financial Management. Based on the results of the BPK Examination, there are several assets / goods issues including the administration and management of the current assets in the Riau Provincial Government which is inadequate with several findings points as follows: The Provincial Government of Riau has not yet assessed the condition of official vehicles as regional running assets so that it has an impact on the condition of vehicles and liability answers to vehicle users, especially the operational vehicles of the Riau Province DPRD Members for the 2009-2014 period, inadequate security and assets are still recorded jointly.               The research objective is to determine the implementation of regional assets in the Riau Provincial Government and determine the factors that influence the implementation of regional asset management in the Riau Province Government 2009-2014. The research method used is descriptive qualitative method with data collection instruments including interviews, observations and documentation studies related to research objectives.               The results of the research on the management of regional assets in the Riau Province DPRD 2009-2014 period have not been maximized, this is because there are still many regulations that are not implemented and there are still many regional assets in the form of vehicles that are not managed properly. The Regional Property Management Cycle starts from Planning and Budgeting to Compensation Claims. The Riau Provincial Equipment Bureau in its task of managing Regional assets in the Riau Province DPRD is constrained by several inhibiting factors, namely as follows: the overall lack of understanding of the Riau Provincial DPRD members in the management of regional property because the regional property information system has not been implemented optimally and does not comply with regulations made in accordance with PP No. 6/2006 and Permendagri No. 17/2007 and the lack of coordination of the equipment bureau with Riau Province DPRD Members in the management of regional assets Keywords: Management, Regional Assets, Operational Vehicles